Dead lions ebook - Herron, Mick (Slough House, 2013)
THE BOOK BEHIND THE SECOND SEASON OF SLOW HORSES , THE APPLE ORIGINAL SERIES STARRING GARY OLDMAN IN HIS EMMY-NOMINATED ROLE AS JACKSON LAMB. The CWA Gold Dagger Award-winning British espionage novel about disgraced MI5 agents who inadvertently uncover a deadly Cold War-era legacy of sleeper cells and mythic super spies. The disgruntled agents of Slough House, the MI5 branch where washed-up spies are sent to finish their failed careers on desk duty, are called into action to protect a visiting Russian oligarch whom MI5 hopes to recruit to British intelligence. While two agents are dispatched on that babysitting job, though, an old Cold War-era spy named Dickie Bow is found dead, ostensibly of a heart attack, on a bus outside of Oxford, far from his usual haunts.  But the head of Slough House, the irascible Jackson Lamb, is convinced Dickie Bow was murdered. As the agents dig into their fallen comrade's circumstances, they uncover a shadowy tangle of ancient Cold War secrets that seem to lead back to a man named Alexander Popov, who is either a Soviet bogeyman or the most dangerous man in the world. How many more people will have to die to keep those secrets buried?